American’t Breathe - Panayides, Angelos (My University, 2022)
The international Cyprus Poster Triennial (CPT) is to be a nonprofit institution that aims to promote and disseminate knowledge and creativity in the field of graphic design by focusing on the poster as a major medium of visual communication. From the early printing of broadsides in the beginning of the 19th century to the present day of the digital era, posters have been influential not only as vehicles that provide information but also as tools responsible for social change, developing awareness on crucial issues, dissemination of revolutionary or political ideas and propaganda. The aspiration of the Cyprus Poster Triennial (CPT) is to establish a graphic design event in the Mediterranean at a place that, on the one hand, can function as a bridge between East and West, and on the other, can bring together designers from all over the world with a variety of perspectives to meet and celebrate the wondrous power of the graphic poster.
Keywords: Biennale; Poster; Exhibition